Impact of ambient air temperature and injection timing on reduction of engine out emissions of DI diesel engine operating under the influence of oxygen enriched hydrogen gas. (1st January 2015) - Premkartikkumar, S.R.; Annamalai, K.; Pradeepkumar, A.R.
The present experimental work is a study of the impact of ambient air temperature and the injection timing of diesel fuel on reduction of engine-out emissions of DI diesel engine, operating under the influence of oxygen enriched hydrogen gas. Here the oxygen enriched hydrogen gas was produced by the process of water electrolysis. The produced gas was aspirated into the combustion process of petroleum diesel along with intake air at the flow rate of 4.6 lpm. The results showed that the fuel consumption got decreased and simultaneously, engine-out emissions came down by the addition of oxygen enriched hydrogen gas. When the ambient air temperature was increased to 35°C, and with retarded injection timing of 19°BTDC, the brake specific energy consumption of the test engine got decreased by 10.59%, unburned hydrocarbon emission by 15.15%, and the NO X emissions by 7.62%.